An integrated pest control strategy against the Asian tiger mosquito in northern Italy: a case study. Issue 1 (13th September 2016) - Baldacchino, Frédéric; Bussola, Francesca; Arnoldi, Daniele; Marcantonio, Matteo; Montarsi, Fabrizio; Capelli, Gioia; Rosà, Roberto; Rizzoli, Annapaola
Abstract: BACKGROUND: In Europe, Aedes albopictus is an invasive mosquito species known to be a major nuisance as well as a vector of a range of arboviruses. A number of studies have indicated that community participation programmes are an effective pest control tool to reduce mosquito populations. However, few studies have evaluated the effectiveness of a community‐based approach in Europe. In this study, we examined two Ae. albopictus control strategies that implemented a community‐based approach in northern Italy: one was a partial intervention that included a public education campaign and the larviciding of public spaces, and the other was a full intervention that additionally included a door‐to‐door campaign. This latter consisted of going door to door actively to educate residents about control measures and deliver larvicide tablets for treating catch basins at home. A site where no intervention measures were carried out was used as a control. RESULTS: In the site where a full intervention was carried out, Ae. albopictus egg density was 1.6 times less than at the site that received partial intervention, and 1.9 times less than at the non‐intervention site. No significant reduction in egg density was achieved in the partial intervention site. CONCLUSIONS: In our study, Ae. albopictus populations were most effectively reduced by larviciding both public and private catch basins. Door‐to‐door education was effective in convincing residents to apply control measures on their property; however, this method was labour intensive and costly. It may be possible to reduce personnel costs by involving volunteers or using a 'hot spot' approach. © 2016 Society of Chemical Industry